Endoscopic clips allow for accurate pre‐operative localisation of colorectal cancer. Issue 10 (28th June 2021) - Parys, Simon; Park, Hyerin; Entriken, Fiona; Ee, Hooi C.; Hodder, Rupert
Abstract: Background: Colorectal cancer is a major cause of morbidity and mortality worldwide. Optimal management of this disease relies upon accurate pre‐operative localisation to allow multidisciplinary discussion and treatment planning. Current pre‐operative localisation methods consist of colonoscopy and computed tomography (CT), which are only 79%–85% accurate. To minimise this error, colonoscopy tattooing is a routine practice to facilitate operative localisation. The aim of this study is to investigate if endoscopic radiopaque clips can more accurately localise the lesions pre‐operatively. Methods: A retrospective case–control study was conducted of patients diagnosed with colorectal cancer at a tertiary hospital between 2017 and 2019. Visualisation rates and accurate localisation rates were compared between patients receiving radiopaque clips and those who had colonoscopy alone. All patients received a tattoo distal to the tumour and a staging CT. Data on patient demographics, tumour demographics, post‐procedure complications and changes to surgical management were collected. Results: Of 285 patients, 245 had tumour localisation with colonoscopy alone and 40 had additional clip localisation. Groups had comparable patient demographics. For patients receiving clips and follow‐up CTs within 14 days, 92% of lesions were visualised and 100% of these lesions were accurately localised. In contrast, colonoscopy only accurately localised 77% of lesions ( p  < 0.01). This resulted in 1.2% of patients requiring an altered operation due to incorrect localisation. No clip‐related complications were reported. Conclusion: Radiopaque clips are a highly accurate and cost‐effective method for localising colorectal cancer with a pre‐operative accuracy rate over 92%. Abstract : A single‐centre retrospective study of 285 colorectal cancer patients was undertaken to investigate if radiopaque clips placed at colonoscopy combined with standard staging computed tomography (CT) could better localise colorectal cancers pre‐operatively, thus facilitating accurate multidisciplinary team discussion and management. The findings confirmed that radiopaque clip combined with CT localised lesions accurately in 92% of cases, significantly better then colonoscopy alone (77%) or CT scan without marker (68%).